(untitled) (Advances in Knowledge Representation, 2021)
This study aims to present the development of a scoping review protocol that will seek to identify and synthesize scientific evidence on the practice of Community Health Workers in the prevention and control of leprosy. The protocol used the method proposed by the Joanna Briggs Institute, Reviewers Manual 2020, which establishes five steps: 1) identification of the research question; 2) identification of relevant studies; 3) selection of studies; 4) data analysis; and, 5) grouping, synthesis and presentation of data. Scoping review in the context of Information Science is an important tool for the recovery and synthesis of knowledge. Thus, it is necessary that the information professional knows this type of literature review, used in the health area and, therefore, can help the multidisciplinary health team in the search and systematization of knowledge